1999
DOI: 10.1021/ja982405d
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of Substituted Phenols Toward Alkyl Radicals

Abstract: The rate constants for the reaction of primary alkyl radicals with substituted phenolic compounds have been measured in benzene or toluene at room temperature by using the radical clock technique. With three representative phenols, containing in the ortho positions substituents of different size, the kinetics of the hydrogen transfer to alkyl radicals was studied at different temperatures to obtain the corresponding Arrhenius parameters. The kinetic solvent effect on the reaction with R-tocopherol was also inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
75
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(86 citation statements)
references
References 39 publications
10
75
1
Order By: Relevance
“…The logarithms of the rate constants for H-atom abstraction are known to be inversely proportional to the BDE(O-H)s. The slope and the y-intercept of these plots are dependent on the nature of the abstracting radicals and on the steric crowding around the phenolic OH group, respectively. [30,32,33] In Figure 5 it is shown that 5b-d are on the same line of unhindered phenols, this being consistent with the presence, in ortho position to the OH group, of only one methyl group in 5b,c and with the absence of any substituent in 5d. Compound 5a is near to the line of 2,6-dimethylphenols, as expected from its structure.…”
Section: Resultssupporting
confidence: 68%
“…The logarithms of the rate constants for H-atom abstraction are known to be inversely proportional to the BDE(O-H)s. The slope and the y-intercept of these plots are dependent on the nature of the abstracting radicals and on the steric crowding around the phenolic OH group, respectively. [30,32,33] In Figure 5 it is shown that 5b-d are on the same line of unhindered phenols, this being consistent with the presence, in ortho position to the OH group, of only one methyl group in 5b,c and with the absence of any substituent in 5d. Compound 5a is near to the line of 2,6-dimethylphenols, as expected from its structure.…”
Section: Resultssupporting
confidence: 68%
“…Even steric protection of the OH group in 2,6-di-tert-butylphenols does not prevent the formation of a hydrogen bond with suitable acceptors, [27] although 1e is often described [28] as a molecule that does not form hydrogen bonds even with strong hydrogen-bond acceptors. Phenols 1a-e have high BDE values when compared to the H-O BDE in nitrous acid and also a fairly good tendency to form hydrogen bonds with the solvent, as indicated by their α H 2 values.…”
Section: Resultsmentioning
confidence: 99%
“…Judging from recent data reported by Pedulli et. al., [39] k 2 should be around 10 6  -1 s -1 at 600 K. This can be followed by combination of phenoxy with methyl radicals to give anisole, plus o-/p-cresols, the latter two compounds after tautomerisation of the respective keto forms (Equation 3). [14] CH 3…”
Section: Discussion (A) Radical-induced Lower-temperature Approachesmentioning
confidence: 99%